Clinicopathologic Characterization of Hypocellular Acute Myeloid Leukemia (AML) Showed Fewer Genetic Abnormalities Involving Cell Proliferation and NPM1 When Compared With Nonhypocellular AML. Issue 3 (22nd October 2020) - Carlsen, Eric; Bailey, Nathanael G; Aggarwal, Nidhi; Illar, Gwendolyn M; Wild, Matthew; Yatsenko, Svetlana A; Rea, Bryan; Liu, Yen-Chun
Abstract: Objectives: Hypocellular acute myeloid leukemia (AML) is uncommon. Despite the prognostic and therapeutic importance of mutational analysis, the mutational landscape of hypocellular AML is not well understood. Methods: We identified 25 patients with hypocellular AML, and 141 patients with nonhypocellular AML were identified as a control group. We applied next-generation sequencing for the first time to profile this entity. Results: The hypocellular AML patients were older than those with nonhypocellular AML ( P = .037). At diagnosis, hypocellular AML had lower leukocyte counts ( P = .012), higher hemoglobin ( P = .003), and lower blast counts in the peripheral blood ( P < .001) and bone marrow ( P = .003). Hypocellular AML was less likely to have mutations involving cell proliferation ( P = .027) and NPM1 ( P = .022) compared with nonhypocellular AML. Hypocellular AML showed a high incidence of spliceosomal mutations and myelodysplastic syndrome-defining chromosome abnormalities (65%), but the incidence was not significantly different from that in nonhypocellular AML. There was no significant survival difference between hypocellular and nonhypocellular AML. Conclusions: To our knowledge, this study is the first to demonstrate hypocellular AML showed fewer genetic alterations involving cell proliferation and NPM1 when compared directly with nonhypocellular AML; this finding likely contributes to the low marrow cellularity in at least a portion of the patients with hypocellular AML.